Hubungan Caring dan Kepuasan Pasien Rawat Inap di Rumah Sakit Islam Banjarmasin - Akhmad Hafidz Fahrezy; Iswantoro Iswantoro; Millati, Rida; Paramitha, Dewi Setya (Jurnal Siti Rufaidah, 2025)
This study aimed to examine the relationship between nurses’ caring behavior and the satisfaction of inpatients at Banjarmasin Islamic Hospital. Caring is the core of nursing practice, encompassing a holistic concern for patients, while patient satisfaction is an important indicator of healthcare quality. This study employed a quantitative research design. The population consisted of all inpatients at Banjarmasin Islamic Hospital, resulting in a total of 100 respondents. The instruments used were a caring behavior questionnaire based on Jean Watson’s theory and a patient satisfaction questionnaire. Data were analyzed using the Spearman Rank test with a significance level of 0.01. The results showed that most nurses were perceived as having good caring behavior, and the majority of patients reported being satisfied with the services provided. Statistical testing revealed a significant relationship between nurses’ caring behavior and inpatient satisfaction (p-value = 0.01; r = 0.504), with the strength of the relationship categorized as moderate. The study concludes that the better the nurses’ caring behavior, the higher the level of patient satisfaction. It is recommended that the hospital continue to enhance nurses’ caring competence through training, supervision, and regular evaluation, so that the quality of nursing services and patient satisfaction can be continuously improved.